2022
DOI: 10.1177/20578911211069496
|View full text |Cite
|
Sign up to set email alerts
|

Corruption – Poverty Nexus: Evidence from Panel ARDL Approach for SAARC Countries

Abstract: The article intends to investigate the relationship between corruption and poverty based on the panel data of SAARC countries over the period 1996–2019. We employed the panel ARDL of pooled mean group (PMG) technique to analyze the data and focus on capability poverty, using the human development index (HDI) as a proxy for poverty. The empirical findings of PMG of the ARDL model suggest that an increase in corruption score (COC) (i.e. decrease in corruption) and increase in women’s labor force participation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Adeleye, Adedoyin, and Nathaniel (2020) and Adeleye, Gershon, et al (2020) discussed the linkage between growth, poverty and inequality. The study found that the growth rate contributes significantly to poverty alleviation in the region the same with (Vinayagathasan & Ramesh, 2022). Mansi et al (2020) found that economic growth significantly negatively impacts EU and Western Balkan poverty.…”
Section: Economic Growth and Poverty Nexusmentioning
confidence: 73%
“…Adeleye, Adedoyin, and Nathaniel (2020) and Adeleye, Gershon, et al (2020) discussed the linkage between growth, poverty and inequality. The study found that the growth rate contributes significantly to poverty alleviation in the region the same with (Vinayagathasan & Ramesh, 2022). Mansi et al (2020) found that economic growth significantly negatively impacts EU and Western Balkan poverty.…”
Section: Economic Growth and Poverty Nexusmentioning
confidence: 73%
“…The autoregressive distributed lags (ARDL) model is considered as one of the most desired second-generation heterogeneous panel data estimators that have been applied to many cointegration analysis. For instance, Pradhan and Bagchi (2012) examined expenditure-GDP nexus in seven SAARC countries, Vinayagathasan and Ramesh (2022) investigates Corruption-Poverty nexus also of SAARC countries, Ismail (2017) analyzed military expenditure and economic growth relation in South Asian countries, etc. In line with M.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Different from studies that establish a bidirectional or unidirectional causality between inflation and poverty, there are few other research efforts that find no causal relationship. Vinayagathasan and Ramesh (2022) report evidence of no causality between inflation and poverty in a panel analysis of eight South Asian countries, covering the 1996-2019 period. Similar results are obtained in a study by Sehrawat and Giri (2018) in India over the period of 1970-2015.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Meanwhile, the research outcomes of the existing research are mixed and inconclusive (Olaniyi et al. , 2023b; Vinayagathasan and Ramesh, 2022; Inegbedion and Obadiaru, 2022; Rizki and Solihati, 2022; Gyeke-Dako et al ., 2022; Sari and Rofiuddin, 2022; Sani and Yahaya, 2021; Sehrawat and Giri, 2018; Yolanda, 2017; Hassan et al. , 2016; Shrestha and Chaudhary, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%